2021
DOI: 10.28991/cej-2021-03091698
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Significance Assessment of Streamflow Elasticity of Major Rivers

Abstract: Impacts of climate change on streamflow have long been an issue of concern for water experts. The main aim of this study is to assess the response of streamflow to precipitation and air temperature. In this study elasticity model was used to compute the precipitation and air temperature elasticity of 6 major rivers in Khyber-Pakhtunkhwa (KP) Province, Pakistan. In contrast to temperature elasticity estimator, box plots of precipitation elasticity estimator have low range and standard deviation leading to great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The stored water will be used in the dry season for agriculture, hydropower, industrial, and domestic purposes. Furthermore, plantations are suggested in the study area to decline the increasing trend of air temperature as the sensitivity of streamflow is higher in the study area (Ahmad et al 2020;Shah et al 2021).…”
Section: Watershed Management Implicationsmentioning
confidence: 99%
“…The stored water will be used in the dry season for agriculture, hydropower, industrial, and domestic purposes. Furthermore, plantations are suggested in the study area to decline the increasing trend of air temperature as the sensitivity of streamflow is higher in the study area (Ahmad et al 2020;Shah et al 2021).…”
Section: Watershed Management Implicationsmentioning
confidence: 99%
“…In Equation ( 2), variables P and Q are quite general and can be used as instantaneous, monthly, or annual values [77][78][79]. In this study, the mean annual values of streamflow Q and precipitation P for the estimation of ε p were utilized.…”
Section: Np (Np) Bivariate Modelmentioning
confidence: 99%
“…Similarly, it was also found that the regression analysis that includes temperature improves the coefficient of determination (R 2 ) [40]. Since all the subsequent research based on multivariate models suggests that multivariate models are more reliable than bivariate elasticity models [39,42,48,[73][74][75][76][77][78][79][80][81][82], it is believed that the multivariate elasticity results of our study are more authentic than the bivariate elasticity results, although there is very small difference between the results as discussed in Section 3.1 above.…”
Section: Bivariate Versus Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change may significantly alter hydrological processes affecting water quality and quantity ( Jamali et al 2013;Abera et al 2018;Ekwueme & Agunwamba 2021;Feistel & Hellmuth 2021;Hassanjabbar et al 2021;Shah et al 2021). Therefore, understanding the impact of other significant drivers such as climate change helps water managers make better contributions and decisions to solve water quality degradation and conserve aquatic ecosystems.…”
Section: Literature Reviewmentioning
confidence: 99%